A simple triple‐band coupled line filtering power divider design. Issue 1 (21st August 2021) - Zhang, Zhuowei; Zhang, Gang; Li, Rui; Zhang, Simin; Chen, Qinzi; Chen, Lu; Yang, Zhenyuan; Tang, Wanchun
Abstract: In this letter, a triple‐band filtering power divider (FPD) is proposed for passive circuit implementation with a good isolation. The proposed triple‐band FPD is composed of coupled microstrip lines by applying a comprehensive design method. Based on the design method and developed topology, the employed coupled microstrip resonators, the input/output feedlines as well as isolated resistor are properly arranged to achieve a desired triple‐band filtering and isolation response. To validate our design concept and method, a triple‐band FPD operating at 2.3–2.33, 2.39–2.42, and 2.5–2.53 GHz is implemented with good return loss and isolation. Measured and simulated results are in good agreement.